Zhilong Huoxue Tongyu Capsules Ameliorate Early Brain Inflammatory Injury Induced by Intracerebral Hemorrhage via Inhibition of Canonical NFкβ Signalling Pathway - Mazhar, Maryam; Yang, Guoqiang; Mao, Linshen; Liang, Pan; Tan, Ruizhi; Wang, Li; Xu, Houping; Yang, Luyin; Ren, Wei; Yang, Sijin (Frontiers in Pharmacology, 2022)
Background: Intracerebral hemorrhage (ICH) is a debilitating and fatal condition with continuously rising incidence globally, without effective treatment available. Zhilong Huoxue Tongyu (ZLHXTY) capsule is a traditional Chinese medicine that is used for ICH treatment in China. However, the evidence based mechanism is not clear. Purpose: To study the protective effects of ZLHXTY capsules against ICH pathogenesis via targetting nuclear factor kappa β (NFкβ) canonical signalling pathway. Methods: C57BL/6J mice ICH models using autologous blood injection were used to study the effect of ZLHXTY (1.4g/kg P.O.) after 24hrs and 72hrs of ICH induction. The neurological scoring, corner turn test and balance beam with scoring was performed to assess neurological damage. Hematoxylin/eosin and nissl staining were used for histopathological evaluation. Levels of TNFα, NFкB, iNOS, COX2, IL1, IL6 were measured using real time qPCR and western blotting. Protein levels of IKKβ and IкBα were analyzed through western blotting. Immunofluorescence for co-expression of NeuN/TNFα, NeuN/NFкB, Iba1/TNFα, and Iba1/NFкB was also performed. Results: Treatment with ZLHXTY capsules after ICH ameliorated inflammatory brain injury after 24 and 72 hrs; revealed by neurological scoring, hematoxylin/eosin and nissl staining. The qPCR and western blot analyses demonstrated significant downregulation of TNFα, NFкB, iNOS, COX2, IL1β and IL6. Further, the IKKβ and IкBα revealed significant downregulation and upregulation respectively in western blot. Immunofluorescence also revealed attenuated expression of TNFα and NFкB in neurons and also low expression of Iba1. Conclusion: ZLHXTY capsules elicit its neuroprotective effect by targetting the NFкβ canonical signalling pathway, thereby ameliorating the ICH induced brain injury.